2013
DOI: 10.1371/journal.pone.0081933
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Activity Coefficients of Free-Solvent for Concentrated Globular Protein Solutions Using Independently Determined Physical Parameters

Abstract: The activity coefficient is largely considered an empirical parameter that was traditionally introduced to correct the non-ideality observed in thermodynamic systems such as osmotic pressure. Here, the activity coefficient of free-solvent is related to physically realistic parameters and a mathematical expression is developed to directly predict the activity coefficients of free-solvent, for aqueous protein solutions up to near-saturation concentrations. The model is based on the free-solvent model, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These calculations were simplified by taking activity coefficients as unity, based on a review of available data [ 18 , 24 , 37 ]. Better approximations for the activity coefficients are required to obtain results that are more accurate.…”
Section: Methodsmentioning
confidence: 99%
“…These calculations were simplified by taking activity coefficients as unity, based on a review of available data [ 18 , 24 , 37 ]. Better approximations for the activity coefficients are required to obtain results that are more accurate.…”
Section: Methodsmentioning
confidence: 99%
“…[46][47][48][49][50][51] However, we have shown that, via our FSB model, the bulk property, osmotic pressure, of self-crowded proteins and crowded binary globular protein solutions can directly provide ion binding and hydration properties of proteins, specifically in the highly crowded regions where the rate of change of osmotic pressure to protein concentration is highly non-linear. [52][53][54][55][56][57][58][59][60][61][62][63] Because the FSB model focuses on protein hydration and ion-binding, it can provide a fortuitous approach in interrogating anion effects on crowded protein solutions.…”
Section: Relevance Of Osmotic Pressure In the Interpretation Of Anionmentioning
confidence: 99%
“…Osmotic pressure does not give direct crystallization information. Nevertheless, a number of researchers have used osmotic pressure to address observed phenomena of proteins in ionic aqueous solutions via protein–protein interactions. However, we have shown that via our FSB model, the bulk property, osmotic pressure of self-crowded proteins and crowded binary globular protein solutions can directly provide ion binding and hydration properties of proteins, specifically in the highly crowded regions where the rate of change of osmotic pressure to protein concentration is highly nonlinear. Because the FSB model focuses on protein hydration and ion binding, it can provide a fortuitous approach in interrogating anion effects on crowded protein solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Protein molecular diffusivity was assumed constant since the working protein conditions can still be considered as dilute such that the respective activity coefficient can be set to 1.0, making the molecular diffusivity independent of protein concentration (McBride and Rodgers, 2013).…”
Section: Protein Uptake Modelmentioning
confidence: 99%